An insight into the pyrolysis process of metal–organic framework templates/precursors to construct metal oxide anode materials for lithium-ion batteries. (16th May 2019) - Li, Ang; Qian, Binbin; Zhong, Ming; Liu, Yingying; Chang, Ze; Bu, Xian-He
Abstract : Two types of MOFs from the same linkers were selected as precursors to obtain Co3 O4 nanomaterials. The structure and component evolution in the pyrolysis process were analyzed to illustrate the structure–activity relationship for the design of Co3 O4 -based anode materials for lithium-ion batteries. Abstract : Metal–organic frameworks (MOFs) have been utilized as templates/precursors for the synthesis of metal oxide anode materials of lithium-ion batteries, due to their large accessible surface, tunable pore size, and various metal centers. However, the same phase of materials derived from different MOFs could show diverse capacities and performances. In this study, aiming at an in-depth understanding of the structural relationship between the precursors and the product, we chose two MOFs with the same linker as templates/precursors for Co3 O4 nanomaterials. The structure and component evolution in the pyrolysis process were analyzed, and the electrochemical properties of the resulting Co3 O4 were studied. The results showed that the concentration of metal centers and the strength of coordination bonds in the MOFs were critical factors that determined the morphology and performances of the resulting material.